2018
DOI: 10.1038/nature25463
|View full text |Cite
|
Sign up to set email alerts
|

Teneurin-3 controls topographic circuit assembly in the hippocampus

Abstract: Brain functions rely on specific patterns of connectivity. Teneurins are evolutionarily conserved transmembrane proteins that instruct synaptic partner matching in Drosophila and are required for vertebrate visual system development. The roles of vertebrate teneurins in connectivity beyond the visual system remain largely unknown and their mechanisms of action have not been demonstrated. Here we show that mouse teneurin-3 is expressed in multiple topographically interconnected areas of the hippocampal region, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
203
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(222 citation statements)
references
References 66 publications
(86 reference statements)
18
203
0
Order By: Relevance
“…Most studies of selective synapse formation have focused on cell-cell recognition between neurons. Several families of neuronal cell adhesion molecules and secreted proteins have been shown to play important roles in synapse specificity (Berns et al, 2018;Chih et al, 2006;Duan et al, 2014;Krishnaswamy et al, 2015;Tran et al, 2009;Zipursky and Sanes, 2010). However, it remains unclear whether the specificity of synapse formation can be entirely explained by an adhesion code among circuit partners, or if other cellular and molecular mechanisms also play an instructive role.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies of selective synapse formation have focused on cell-cell recognition between neurons. Several families of neuronal cell adhesion molecules and secreted proteins have been shown to play important roles in synapse specificity (Berns et al, 2018;Chih et al, 2006;Duan et al, 2014;Krishnaswamy et al, 2015;Tran et al, 2009;Zipursky and Sanes, 2010). However, it remains unclear whether the specificity of synapse formation can be entirely explained by an adhesion code among circuit partners, or if other cellular and molecular mechanisms also play an instructive role.…”
Section: Introductionmentioning
confidence: 99%
“…To ensure evolutionary economy, these events can be coordinated through reuse of molecular cues and mechanisms. These mechanisms are conserved from peripheral to central synapses in Drosophila; work has also shown similar roles in mammalian nervous systems for wiring and synapse organization (Berns et al, 2018;Dharmaratne et al, 2012;Leamey et al, 2007;Mosca, 2015), suggesting mechanistic conservation across multiple species as well. As such, the Teneurins are an evolutionary constant, working at multiple levels to ensure nervous system development.…”
Section: Future Directionsmentioning
confidence: 87%
“…As alternative splicing prevents the formation of the Tenm2/Lphn3 interaction by hiding it rather than destroying it, it is plausible that the +SS isoform enables other Tenm2 interactions that the -SS isoform cannot mediate. Indeed, the trans-dimerization of Tenm2 was reported to occur only by the +SS isoform (Berns et al, 2018); and previous studies suggested that Tenm2 +SS isoform should interact with unknown ligands in order to induce inhibitory synapses (Li et al, 2018). This speculative model explains the currently available data.…”
Section: Discussionmentioning
confidence: 99%
“…1C) (Feng et al, 2002;Oohashi et al, 1999;Vysokov et al, 2016). Tenm's have central roles in tissue polarity, embryogenesis, heart development, axon guidance, and synapse formation (Berns et al, 2018;Boucard et al, 2014;Doyle et al, 2006;Hong et al, 2012;Levine et al, 1994;Mosca and Luo, 2014;Silva et al, 2011;Woelfle et al, 2016); and are linked to various diseases including neurological disorders, developmental problems, various cancers and congenital general anosmia (Aldahmesh et al, 2012;Alkelai et al, 2016;Chassaing et al, 2016;Graumann et al, 2017;Hor et al, 2015;Talamillo et al, 2017;Ziegler et al, 2012). Lphn's (Lphn1-3 in mammals) belong to the adhesion-type Gprotein coupled receptor (GPCR) family (Krasnoperov et al, 1996;Lelianova et al, 1997) (Sugita et al, 1999) and have a large N-terminal ECR (>800 amino acids) in addition to their signaling seven-pass transmembrane domain and cytoplasmic tail ( Fig.…”
Section: Introductionmentioning
confidence: 99%